2010
DOI: 10.1002/pssa.201026306
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and phase transition of lead‐free (Bi1/2Na1/2)TiO3‐based ferroelectrics via different Li+ introduction sources

Abstract: Lead‐free 0.85(Bi1/2Na1/2)TiO3‐0.10(Bi1/2K1/2)TiO3‐0.05BaTiO3 (BNKBT) ceramics with Li2CO3 or (Bi1/2Li1/2)TiO3 (BLT) added were fabricated by conventional solid oxide route. The XRD analysis indicated that Li2CO3 introduction led to increasing fraction of tetragonal phase while BLT introduction gave a reverse tendency. Meanwhile, the depolarization temperature Td of Li2CO3‐added BNKBT ceramics was clearly enhanced, while that of BLT‐added BNKBT ceramics went down as the added amount increased. The similarity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This conrms that the diffuse phase transition is stronger for the compositions with a higher Al 2 O 3 content. Several methods to determine the thermal depolarization temperature (T d ) can be found in the literatures 14,[41][42][43][44] including the thermally stimulated depolarization current (TSDC), temperature dependent in situ d 33 , dielectric permittivity and dielectric loss, piezoelectric resonance measurements, and high-temperature in situ XRD. 14 However, the TSDC method is one of the most popular techniques.…”
Section: Dielectric Properties and Phase Transitionmentioning
confidence: 99%
“…This conrms that the diffuse phase transition is stronger for the compositions with a higher Al 2 O 3 content. Several methods to determine the thermal depolarization temperature (T d ) can be found in the literatures 14,[41][42][43][44] including the thermally stimulated depolarization current (TSDC), temperature dependent in situ d 33 , dielectric permittivity and dielectric loss, piezoelectric resonance measurements, and high-temperature in situ XRD. 14 However, the TSDC method is one of the most popular techniques.…”
Section: Dielectric Properties and Phase Transitionmentioning
confidence: 99%
“…It was found that increase in the bismuth lithium titanate content leads to a decrease in the Curie temperature in the system (Na 0.5 K 0.5 )NbO 3 . In contrast to these data, the authors of [7] showed that the introduction of lithium ions to the sodium-potassium sublattice leads to an increase in the Curie temperature in the system [Bi 0.5 (Na 1-x-y K x Li y ) 0.5 ]TiO 3 . It was shown that increasing lithium-bismuth titanate concentration leads to an increase in resistance and Curie temperature in Nb-doped PTCR solid solutions based on Ba 1−x Bi 0.5x Li 0.5x Ti 1-y Nb y O 3 from 120ºC to 150ºC in the range of 0≤x≤0.03 [8].…”
Section: Introductionmentioning
confidence: 92%